Nutrition in cacao (Theobroma cacao L.) crops: What determining factors should be considered? - Laura Michell Carmona Rojas; Edwin Antonio Gutiérrez Rodríguez; Ana Maria Henao Ramirez; Aura Ines Urrea Trujillo (Revista de la Facultad de Agronomía, 2022)
Cacao (Theobroma cacao L.) is an important commercial crop and agricultural commodity worldwide; for some Latin American countries, it is an essential part of export products. In Colombia, this crop has promising conditions to extend and strengthen this agriculture sector. However, their productivity is low under current agricultural practices, mainly due to insufficient modernization and inadequate or no management of their nutritional schemes. This publication  reviewed the different findings currently in the scientific literature regarding the factors that determine the nutritional status of cacao plants, such as the function and distribution of minerals, nutritional efficiency, soil properties, establishment systems, organic and organic and inorganic sources examined. Additionally, it highlighted the importance of using and expanding diagnostic tools to determine nutritional needs and the design of effective programs according to the particular conditions of each region and the genotypes planted. This conceptual journey highlights the existing theoretical and experimental gap in the identification of the factors that determine the nutritional status of the plantations and their effect on the implementation of the fertilization programs used today. Information together provides elements to adequately address this agronomic practice and the economic impact on farmers and the cacao production chain.